2022
DOI: 10.3389/fonc.2022.955313
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota composition in chemotherapy and targeted therapy of patients with metastatic colorectal cancer

Abstract: Studies have reported the effects of the gut microbiota on colorectal cancer (CRC) chemotherapy, but few studies have investigated the association between gut microbiota and targeted therapy. This study investigated the role of the gut microbiota in the treatment outcomes of patients with metastatic CRC (mCRC). We enrolled 110 patients with mCRC and treated them with standard cancer therapy. Stool samples were collected before administering a combination of chemotherapy and targeted therapy. Patients who had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 76 publications
1
12
0
Order By: Relevance
“…Although studies with more diverse populations and larger sample sizes are required to determine whether population-specific bacteria are responsible for CRC progression and are associated with clinicopathological characteristics, our results strongly suggest that P. intermedia and F. nucleatum are critical pathogens for CRC development in individuals of Han Chinese origin. Moreover, our recent study demonstrated that F. nucleatum is closely associated with treatment outcomes in patients with metastatic CRC receiving chemotherapy and targeted therapy [41].…”
Section: Discussionmentioning
confidence: 94%
“…Although studies with more diverse populations and larger sample sizes are required to determine whether population-specific bacteria are responsible for CRC progression and are associated with clinicopathological characteristics, our results strongly suggest that P. intermedia and F. nucleatum are critical pathogens for CRC development in individuals of Han Chinese origin. Moreover, our recent study demonstrated that F. nucleatum is closely associated with treatment outcomes in patients with metastatic CRC receiving chemotherapy and targeted therapy [41].…”
Section: Discussionmentioning
confidence: 94%
“…In addition, chemotherapy (5-fluorouracil/oxaliplatin) markedly increases the ratio of relative abundance of the Firmicutes/Bacteroidetes, inducing greater disturbance of intestinal microbiota ( Chang et al, 2020 ). Although the gut microbiota of patients who had a partial response for targeted therapy (bevacizumab/cetuximab) exhibits significantly higher α-diversity than that of the progressive disease group, the overall intestinal microbiota is still disordered ( Chen et al, 2022 ). Alteration in the intestinal microbiota affects the metabolic pathway of glycerophospholipid, thereby regulating the therapeutic potential of the immunotherapy (PD-1 antibody) in MSS-type CRC tumor-bearing mice ( Xu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Even so, the previous study has also shown that the Bifidobacterium genus accumulated in ankylosing spondylitis patients [ 17 ]. Another study investigated the role of the gut microbiota in the treatment outcomes of patients with metastatic CRC (mCRC) and reported that Lactobacillus and Bifidobacterium species exhibited higher abundance in the progressive disease (PD) group than in the partial response (PR) group [ 28 ]. Additionally, some Bacteroides species have been demonstrated to exhibit significantly lower relative abundance in patients with UC than in healthy controls [ 29 ].…”
Section: Discussionmentioning
confidence: 99%